Iris Detection Using Segmentation Techniques - Taneja, Neeti; Shabaz, Mohammad; Khajuria, Vinayak (International Journal of Computer Sciences and Engineering, 2018)
This paper introduces an approach to be adopted for the detection of iris from the medical image of human eye. The microscopic image of human eye is taken which consists of number of features such as pupil, retina, iris etc. Firstly image pre-processing is done on the input image so as to remove unwanted noise from it and then various image segmentation techniques such as edge detection, Hough transform etc. are applied for the efficient identification of the inner and outer boundary of iris. To efficiently detect iris boundary, accurate evaluation of circumference of iris in the human eye is required.